KONTRIBUSI BAHASA SUNDA BAGI PENGEMBANGAN BAHASA INDONESIA - Zaenal Arifin (Sawo Manila, 2010)
Indonesian (Bahasa) influences province languages, such as Sundanese, andvise versa. This language still needs the contribution of new vocabulariesby various sources. For that reason, the material of Indonesian terms takesthree most important groups of language; Malaya, neighboring nations, andforeign languages. Therefore, there are several Sundanese words not given Sdlabel because the contribution of Sundanese in the enrichment of Indonesianapproximate around 300 vocabularies.